THE EFFECTIVENESS OF THE ELECTRONIC SIGNATURE IN ESTABLISHING PAYMENT BY ELECTRONIC CHEQUE BETWEEN EVIDENTIARY REQUIREMENTS AND PUBLIC ORDER REGULATIONS: A COMPARATIVE LEGAL ANALYSIS - Hadjadj Sabrina (International Journal of Innovative Technologies in Social Science, 2024)
The use of the Internet opens up huge horizons for commercial transactions, but at the same time it carries with it risks that may threaten the values and rights of individuals. Perhaps the most important of them appears in the creation of legal proof of the existence of those transactions concluded over the network, the content of which contains all the elements required by law, therefore, the problems of legal proof of electronic transactions - including the electronic check - are at the forefront of the challenges facing these transactions, given that the existing rules of proof did not know of the supports on which the written writing of the transactions was recorded except the paper support (official and customary documents).The importance of developing an appropriate legal framework to regulate all issues of electronic evidence has increased, which sets the legal conditions and technical and technical controls to create evidence of an electronic nature, capable of proving the existence of these transactions, its content is to ensure the integrity of the information exchanged, as well as determining the identity of the parties to the transaction. There is no doubt that achieving that goal depends on creating a safe environment within the validity of the expression of the contractual will, which guarantees the safety of the documents exchanged from any modification or distortion of their content.